2014
DOI: 10.4314/ajtcam.v11i3.32
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antinociceptive Effect of the Ethanolic Extract of <i>Punica Granatum</i>

Abstract: Background: There are severe adverse effects of analgesic drugs on human body. Extraction of analgesic drugs from natural products has therefore become the prime objective of the study. In this study, we aimed to evaluate the antinociceptive activity of the pomegranate fruit. Materials and Methods: Antinociceptive activity of ethanol pomegranate extract was examined using three models of pain: the writhing test, the hot tail flick test and the plantar test. The ethanolic extract of pomegranate was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The pomegranate fruit contains a rich source of compounds with antioxidant properties, of which a majority is present in the juice as anthocyanins [ 33 ]. Although anthocyanin has not been previously studied as an alternative form of non-opioid substitution therapy, previous studies have substantiated the benefits of anthocyanin which include its analgesic [ 34 ] and anti-nociceptive [ 35 , 36 ] effects as well as its use in neurodegenerative diseases [ 37 , 38 ]. Additionally, pomegranate-derived anthocyanin with a concentration of 0.15% in the present study was shown to be a potential source of antioxidant by scavenging the free radicals or preventing lipid oxidation, thereby acting as a non-opioid substitution for various in-vitro and in-vivo studies [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pomegranate fruit contains a rich source of compounds with antioxidant properties, of which a majority is present in the juice as anthocyanins [ 33 ]. Although anthocyanin has not been previously studied as an alternative form of non-opioid substitution therapy, previous studies have substantiated the benefits of anthocyanin which include its analgesic [ 34 ] and anti-nociceptive [ 35 , 36 ] effects as well as its use in neurodegenerative diseases [ 37 , 38 ]. Additionally, pomegranate-derived anthocyanin with a concentration of 0.15% in the present study was shown to be a potential source of antioxidant by scavenging the free radicals or preventing lipid oxidation, thereby acting as a non-opioid substitution for various in-vitro and in-vivo studies [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate extract and its fractions were prepared with references to methods of [10]. The whole fruits were cleaned, freeze-dried and grounded into powder using a blender.…”
Section: Extraction Methodsmentioning
confidence: 99%
“…In our previous work, we have affirmed that the crude ethanol extract was able to produce significant analgesic effect [10]. The present study was undertaken to provide further pharmacological insight into the active fraction, and the mechanisms of analgesic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The tail immersion test is used to determine both centrally acting analgesics (Ramabadran et al, 1989), like diclofenac Na (Schweizer and Brom, 1985) and peripherally acting analgesics like NSAIDs which inhibit cyclooxygenase in peripheral tissues, thereby interfering with the mechanism of transduction of primary afferent nociceptors (Saad et al, 2014). The results observed for the tail immersion test clearly showed that the ethanolic extract of C. pallida possessed a dose-dependent anti-nociceptive activity.…”
Section: Discussionmentioning
confidence: 97%